A Meta-thematic Synthesis of Problem Posing as an Instructional Approach in Mathematics Education - Balacuit, Ian Cesar Panawan; Oledan, Alexis Michael B. (Universitas Islam Negeri Sunan Kudus, 2025)
Problem posing has garnered increasing attention from mathematics education researchers due to its positive impact on students' learning outcomes. However, the extent of these outcomes has not been comprehensively synthesized. Therefore, this study conducted a meta-thematic synthesis to consolidate qualitative evidence on the impacts of the problem-posing approach on students’ learning and their experiences during its implementation. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, a systematic search of literature published between 2010 and 2024 was conducted through Google Scholar. From 207 studies screened, 16 met the inclusion criteria and were analyzed through a meta-thematic synthesis. Findings revealed that the effects of problem posing on students' learning in mathematics can be categorized into cognitive and socio-emotional effects. Cognitive effects include positive changes in problem-solving, creative thinking, mathematical understanding, and argumentation skills. The socio-emotional domain includes the development of productive beliefs, positive mindsets, and affective engagement in learning. Furthermore, two overarching themes emerged regarding students’ engagement with problem-posing tasks: (1) strategies for participating in problem-posing activities, and (2) perceptions of the instructional approach itself. The results affirm that the problem-posing approach contributes to holistic student development by simultaneously fostering cognitive growth and nurturing positive learning dispositions. The findings suggest that integrating the problem-posing approach in the classroom is a sound pedagogy to promote holistic student development. Pendekatan pemecahan masalah telah menarik perhatian yang semakin besar dari para peneliti pendidikan matematika karena dampaknya yang positif terhadap hasil belajar siswa. Namun, sejauh mana dampak tersebut belum disintesis secara komprehensif. Oleh karena itu, studi ini melakukan sintesis meta-tematik untuk mengkonsolidasikan bukti kualitatif mengenai dampak pendekatan pemecahan masalah terhadap pembelajaran siswa dan pengalaman mereka selama implementasinya. Mengikuti kerangka kerja Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), dilakukan pencarian sistematis terhadap literatur yang diterbitkan antara tahun 2010 dan 2024 melalui Google Scholar. Dari 207 studi yang disaring, 16 memenuhi kriteria inklusi dan dianalisis melalui sintesis meta-tematik. Temuan menunjukkan bahwa dampak pendekatan pemecahan masalah terhadap pembelajaran matematika siswa dapat dikategorikan menjadi dampak kognitif dan sosial-emosional. Dampak kognitif meliputi perubahan positif dalam pemecahan masalah, berpikir kreatif, pemahaman matematika, dan keterampilan berargumen. Domain sosial-emosional meliputi pengembangan keyakinan produktif, mindset positif, dan keterlibatan afektif dalam pembelajaran. Selain itu, dua tema utama muncul terkait keterlibatan siswa dalam tugas-tugas pemecahan masalah: (1) strategi untuk berpartisipasi dalam aktivitas pemecahan masalah, dan (2) persepsi terhadap pendekatan instruksional itu sendiri. Hasil penelitian menegaskan bahwa pendekatan pemecahan masalah berkontribusi pada perkembangan holistik siswa dengan sekaligus mendorong pertumbuhan kognitif dan menumbuhkan disposisi belajar yang positif. Temuan ini menyarankan bahwa mengintegrasikan pendekatan pemecahan masalah di kelas merupakan pendekatan pedagogis yang efektif untuk mempromosikan perkembangan holistik siswa.